2017
DOI: 10.12659/msm.904366
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Promoter Methylation of Protocadherin8 (PCDH8) in Serum is a Potential Prognostic Marker for Low Gleason Score Prostate Cancer

Abstract: BackgroundPCDH8 is a newly-discovered suppressor gene that is frequently inactivated by aberrant methylation in several human cancers, including prostate cancer. The identification of PCDH8 methylation can be used as a potential predictive biomarker. Prostate cancer patients with high Gleason score are considered as being at high risk for tumor recurrence and progression, and adjuvant therapy is often routinely performed in clinical practice. In the present study, we did not measure the methylation of PCDH8 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…21,22 Recent studies showed that PCDH8, PCDH10 and PCDH17 acted as tumor suppressors in a variety of human cancers. [23][24][25][26][27][28][29][30][31][32][33][34] PCDH9 is another member of the PCDH family located in the 13q21.32 of human genome. Previous studies demonstrated that PCDH9 was down-regulated in cancers, such as glioblastoma, hepatocellular carcinoma and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Recent studies showed that PCDH8, PCDH10 and PCDH17 acted as tumor suppressors in a variety of human cancers. [23][24][25][26][27][28][29][30][31][32][33][34] PCDH9 is another member of the PCDH family located in the 13q21.32 of human genome. Previous studies demonstrated that PCDH9 was down-regulated in cancers, such as glioblastoma, hepatocellular carcinoma and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, cfDNA methylation of the APC, GSTP1, RASSFI, MDRI and PTGS2 genes was associated with overall survival time in men with advanced PCa [60]. Additionally, MSP on a cohort of n = 117 patient serum samples showed that PCDH8 methylation was an independent predictive risk factor for BCR-free survival (p< 0.007) in low GS (< 7) PCa patients after surgery [169]. Overall, these studies highlight the potential value of DNA methylation biomarkers in cfDNA as prognostic indicators of relapse.…”
Section: Blood-based Methylated Prognostic Biomarkers For Cfdna Testingmentioning
confidence: 94%
“…Patients in the same stage all received the same standard treatment. Peripheral blood samples (10 ml) were collected within one week before surgery, and centrifuged at 1800 g for 10 min [18]. Sera were collected and stored at -80 °C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction, bisulfite conversion and methylation specific PCR (MSP). DNA was extracted from sera of patients according to the instructions of the QIAmp DNA Blood Mini Kit (Tiangen Biotech, China) [18], and the isolated DNA was modified by bisulfite using EZ DNA Methylation-Gold kit (Zymo Research, USA). MSP was used to detect the methylation status of T-cadherin in sera.…”
Section: Methodsmentioning
confidence: 99%